Return International Migration and Geographical Inequality: The Case of Egypt - Barry McCormick; Jackline Wahba (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
This paper explores entrepreneurship amongst return migrants, how their business locations and characteristics differ from other businesses, and the implications for rural-urban inequality. First, we examine, amongst returnees, the determinants of investment in a project/enterprise. Second, we study the impact of return migration on the characteristics and nature of non-farm small enterprises using a sample of return migrants and non-migrant owners of enterprises. Our data indicate that although the share of return migrants originating in urban areas is almost equal to those from rural areas, and that migrants tend to return to their origin region, urban areas benefit more than rural areas from international savings. The empirical evidence suggests that ?
Keywords: 330; return migration; remittances; developing countries; rural-urban inequality